LOS ANILLOS TURÍSTICOS COMO FACTOR GENERADOR DE TURISMO EN LOS MUNICIPIOS DE BOYACÁ (Revista cientifica In Vestigium Ire, 2016)
Tourism is recognized as an economic activity impact on the regions for their rapid development and economic growth, such as appropriate the development of this activity change perspectives on the management of natural resources, transforming the paradigms regarding the use resource and cultural aspects. (National Council for Economic and Social Policy, 2005).In the Department of Boyacá with the purpose of promoting tourism in the region, taking advantage of natural resources, geographic position and cultural aspects that owns the provincial government boost a project called “The Tour Boyacá Rings” as stated in the plan departmental development, “Boyacá is the duty of all” 2004- 2007. This research aims to establish how far these rings have enabled the development of tourism in each of the municipalities of Boyacá included in them and what impact it has had on the people of the region; because it shows that many municipalities have been little visited by tourists and is therefore important to determine the shortcomings that have prevented the projected impact.
Keywords: Tourism; Tourist Ring; plan development; economic growth; sustainability